IMPLEMENTASI METODE 5S PADA DIVISI GUDANG BARANG JADI (Studi Kasus Pada PT. X) - Elfitria Wiratmani (Faktor Exacta, 2010)
PT X is a company engaged in public procurement electrical appliances for the home network connection (SR). Low Voltage (JTR), Medium Voltage Networks (JTM), for about providing good service to customers is absolutely necessary corrective steps to reduce activities that do not have tembah value. The purpose of this study was to perform the design and implementation of 5S in warehouse division of finished goods so as to create the optimal workspace. Implementations that have been undertaken include stock issued death from the work area, provide the name of the label on the storage rack of finished goods, making lines on the floor, classifying goods, designing the lay out based on the frequency rate of movement of goods. Implementation results are then evaluated by means of comparison between before and after implementation. The results obtained after the design and implementation dilakuakn produce good performance. This result can be proved by the results of the photo documentation and results of calculations of time before and after implementation. The results can be obtained t to 12.68 and the results obtained after implementation is 2.04. So clearly there is a change after the implementation. Process in the preparation of P (Purchase Order) faster.